Analysis Of The Impact Of Muhammadiyah Khitah On The Younger Generation A Literacy Study - Suwardi, Suwardi; Jandra, Mifedwil (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This study analyzes the impact of Muhammadiyah's Khittah on the younger generation, focusing on its role and implementation in shaping their character and social participation. Khittah Muhammadiyah, as the basic guideline of the organization, emphasizes moderate and progressive Islamic values, which are relevant in facing the challenges of modernization and globalization. Through adaptive education and da'wah programs, Muhammadiyah seeks to instill these values in the younger generation, so that they can play an active role in community development. The results of the analysis show that the understanding and internalization of the Muhammadiyah Khitah that the Muhammadiyah Khithah has a significant impact on the younger generation, both in terms of understanding, behavior, and participation in the organization. Despite the challenges in its implementation, the efforts made by Muhammadiyah to support the younger generation in understanding Khithah should be appreciated. Encourage the younger generation to engage in social activities, have a tolerant attitude, and think critically in dealing with contemporary issues. In addition, the da'wah approach that utilizes digital media has proven to be effective in reaching and influencing the mindset of generation Z. Thus, Khittah Muhammadiyah plays a significant role in shaping the character of the young generation who are noble, insightful, and ready to face the challenges of the times.